Regularities of Modifying, Morphology and Properties of Thermoplastics Containing Polyvinylpyrrolidone - Levytskyi, Volodymyr; Masyuk, Andrii; Jr, Mykhailo Bratychak; Chopyk, Nataliia (Видавництво Львівської політехніки, 2023)
Досліджено особливості модифікування тер¬мопластів поліаміду 66/6 і полістирену полівінілпіролідоном у в’язкотекучому стані. За допомогою інструментальних методів виявлено зміни морфології та фазових переходів модифікованих матеріалів. Визначено вплив модифікатора на міцність і теплофізичні властивості досліджуваних термопластів.

The peculiarities of modifying polyamide 66/6 and polystyrene thermoplastics with polyvinylpyrrolidone in the viscous state have been studied. By applying in-strumental methods, the changes in morphology and phase transitions of modified materials have been revealed. The influence of the modifier on the strength and thermo-physical properties of the researched thermoplastics was determined.
Закономірності модифікування, морфологія та властивості термопластів, що містять полівінілпіролідон
Keywords: модифікація; сумісність; полістирол; поліамід 66/6; полівінілпіролідон; modifying; compatibility; polystyrene; polyamide 66/6; polyvinylpyrrolidone